Education and social change in colonial Indonesia (Ohio University Center for International Studies)
Stencil. 1. Paul W. van der Veur, Progress and procrastination in education in Indonesia prior to World War II. - The social and geographica origins of Dutch-educated Indonesians. Ed. and annotated by P.W. van der Veur. Transl. by Lian The. 1969. XIV, 49 p. - With graph. and tabs.